2009
DOI: 10.1128/aem.02779-08
|View full text |Cite
|
Sign up to set email alerts
|

Failure To Detect Helicobacter pylori DNA in Drinking and Environmental Water in Dhaka, Bangladesh, Using Highly Sensitive Real-Time PCR Assays

Abstract: The main transmission pathway of Helicobacter pylori has not been determined, but several reports have described detection of H. pylori DNA in drinking and environmental water, suggesting that H. pylori may be waterborne. To address this possibility, we developed, tested, and optimized two complementary H. pylorispecific real-time PCR assays for quantification of H. pylori DNA in water. The minimum detection level of the assays including collection procedures and DNA extraction was shown to be approximately 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 50 publications
1
41
1
2
Order By: Relevance
“…In 2007, Ahmed et al indicated that the risk of H. pylori infection can be reduced by improving personal hygiene and regular use of boiled drinking water [20]. On the other hand, Janzon et al reported the less likely involvement of drinking water in a South Asian region [21].…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, Ahmed et al indicated that the risk of H. pylori infection can be reduced by improving personal hygiene and regular use of boiled drinking water [20]. On the other hand, Janzon et al reported the less likely involvement of drinking water in a South Asian region [21].…”
Section: Resultsmentioning
confidence: 99%
“…The resection material was used for isolation of lamina propria lymphocytes and for RNA extraction. For each patient, the H. pylori status was evaluated by different tests, including culture on Columbia-Iso agar plates, quantitative real-time polymerase chain reaction (PCR) [26], and serology tests, where H. pylori status was determined by in-house enzyme-linked immunoassay (ELISA) methods [27], as well as with an EIA-G III ELISA kit (Orion Diagnostics, Finland) and summarized in Table 1. There were no differences in any of the subsequent analyses between H.p.…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%
“…Although several studies have shown the presence of H. pylori in household water, there is little evidence to support that drinking water is a frequent source of new H. pylori infections. Indeed, in a study in a heavily infected population in rural Bangladesh no H. pylori DNA could be detected in any household or environmental water samples using highly sensitive real-time polymerase chain reaction techniques, even though the samples were collected during the peak seasons of new H. pylori infections in the area (Janzon et al, 2009b).…”
Section: Epidemiology and Transmission Of H Pylori Infection In Humansmentioning
confidence: 99%